Seronegative atypical anti-glomerular basement membrane crescentic glomerulonephritis - Adapa, Sreedhar (Ann Transl Med, 2019)
A 46-year-old female presented with a chief complaint of fatigue and intermittent painless gross hematuria for one month. The patient was fluid overloaded on physical examination and noted to be in acute renal failure with a serum creatinine of 10.8 mg/dL. The patient was emergently started on hemodialysis. Serologies were negative for antinuclear antibody (ANA), anti-neutrophilic cytoplasmic antibody (ANCA), and anti-glomerular basement membrane (anti-GBM) antibody. However, renal biopsy revealed 90% glomerular involvement by temporally heterogeneous crescents ranging from cellular to fibrous. Immunofluorescence studies revealed strong, linear glomerular capillary wall staining for immunoglobulin G (IgG). Although the patient was treated with pulse dose steroids and cyclophosphamide, the patient ultimately developed infectious complications from immunosuppression, and treatment was terminated. This case highlights the atypical presentation of anti-GBM disease diagnosed based on renal biopsy with negative serologies. Although rare, the possibility of atypical anti-GBM antibodies which are not detected by standard commercial assays should be considered in such cases.